2007
DOI: 10.1063/1.2431400
|View full text |Cite
|
Sign up to set email alerts
|

Europium luminescence enhancement in Al2O3:Eu3+ powders prepared by direct combustion synthesis

Abstract: The luminescence properties of Eu3+:Al2O3 powders prepared via low temperature direct combustion synthesis was investigated. It was observed that the heat treatment of the powders modifies the dynamics of the radiative transition D05→F27 of Eu3+ (1.0mol%) and produces an enhancement of the luminescence intensity by nearly one order of magnitude. The luminescence enhancement is attributed to the presence of Eu3+ in α-Al2O3 crystalline phase as the heat treatment drastically reduces the amount of amorphous Al2O3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…This large value is indicative of low-symmetry crystal fields near Eu 3+ sites. The emission profile is very similar to that obtained in the Eu 3+ -doped Al 2 O 3 sample annealed in air [21] that presents only a-phase. Low-temperature siteselective spectroscopy performed in our powder showed that Eu 3+ ions are incorporated into C 3v Al 3+ sites in aAl 2 O 3 [22].…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…This large value is indicative of low-symmetry crystal fields near Eu 3+ sites. The emission profile is very similar to that obtained in the Eu 3+ -doped Al 2 O 3 sample annealed in air [21] that presents only a-phase. Low-temperature siteselective spectroscopy performed in our powder showed that Eu 3+ ions are incorporated into C 3v Al 3+ sites in aAl 2 O 3 [22].…”
Section: Methodssupporting
confidence: 76%
“…Recently, we observed luminescence enhancement by energy transfer between RE ions in assynthesized Tb 3+ :Ce 3+ [19] and Eu 3+ :Tb 3+ [20] alumina powders containing a-and g-Al 2 O 3 phases. We also reported the observation of luminescence enhancement of Eu 3+ -doped Al 2 O 3 powders after heat treatment of the sample at 1300 1C for 2 h [21].…”
Section: Introductionmentioning
confidence: 93%
“…It is used in commercial blue phosphors, such as BaMgAl 10 O 17 [11]. Various dielectric hosts in the form of nano-powders [12][13][14][15][16], films [17][18][19], crystals [20][21][22], glasses [23][24][25][26][27] and glass-ceramics (GCs) [28][29][30][31][32][33][34][35][36][37] were studied for Eu-doping to improve the emission efficiency, as well as to tune the color properties; and the list is ever growing.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases there is a short and a long time response component, but the relative amplitude associated with each of them changes drastically in particular for those films doped with Bi 3 þ ions in which the short component becomes dominant in a noticeable way. Previous works for time decay behavior for Eu 3 þ doped Al 2 O 3 phosphors have reported similar short ($ 0.5) and long ($ 1.7) decay times which have been directly linked to the presence of Eu 3 þ ions in an α-Al 2 O 3 or a γ-Al 2 O 3 phase for the short and long decay times respectively [25]. The films studied in this work are amorphous, thus it is possible that the short range arrangement around the Eu 3 þ ions could be similar to one or the other phase in such way that they coexist in the same sample, although the introduction of Bi in particular seems to affect mainly that part associated with the long time response of the PL.…”
Section: Resultsmentioning
confidence: 91%